Enhancing Reading Comprehension through Gamification-Based Task-Based Language Teaching (TBLT) in Online Learning Environments - Wibowo, Amiruddin Hadi; Munir, Ahmad; Suhartono (Proceeding International Conference on Education, 2024)
Online learning has been popular to keep learners engaged and enhanced their reading comprehension. This study investigates the effectiveness of using online gamification-based Task-Based Language Teaching (TBLT) to improve learners' reading comprehension, motivation, and engagement. The research was conducted in an online English course for 30 undergraduate EFL learners. The course incorporated gamification elements such as points, badges, and leaderboards within the TBLT framework to encourage active participation and reading comprehension. Data were collected through interviews, observations, and document analysis, focusing on students' performance, motivation, and engagement during the course. The findings revealed that gamification-based TBLT significantly enhanced learners' motivation and engagement by fostering a sense of achievement through rewards. Learners showed improved reading comprehension, demonstrating a better ability to understand, summarize, and analyze texts. Immediate feedback adjust students with strategies and improve their performance in real-time, while the collaborative nature of the gamified environment promoted social interaction and peer learning. The study concludes that gamification-based TBLT is an effective approach to enhancing reading comprehension in online learning environments. Future research is recommended to explore the long-term effects of gamification on learner retention and the impact of task complexity on advanced learners.